2016
DOI: 10.5935/0103-5053.20160188
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Detection of Adulterated Olive Oil in Full Bottles Using Time-Domain NMR Relaxometry

Abstract: A fast procedure using time-domain nuclear magnetic resonance (TD-NMR) to detect olive oil adulteration with polyunsaturated vegetable oils in filled bottles is proposed. The 1 H transverse relaxation times (T 2 ) of 37 commercial samples were measured using low-field nuclear magnetic resonance (LF-NMR) spectrometer and a unilateral nuclear magnetic resonance (UNMR) sensor. Results obtained with LF-NMR revealed better feasibility when compared with the UNMR sensor, with higher signal-to-noise (S/N) ratio and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
(18 reference statements)
1
13
0
1
Order By: Relevance
“…Thus, different analytical techniques have been developed to detect olive oil adulterations (e.g., MALDI-TOF/MS technique; mid infrared, Raman, fluorescence or visible spectroscopy; DNA-targeted approaches; ion mobility spectrometry; nuclear magnetic resonance; dielectric technique; ultrasounds technique; gas chromatography; etc. ), namely to identify and/or quantify the addition of other vegetable oils like camellia, canola, corn, grapeseed, hazelnut, peanut, rapeseed, soya, sesame, soybean and sunflower oils (De Melo Milanez and Pontes, 2015;Sun et al, 2015;Alouache et al, 2016;Jabeur et al, 2016;Kalaitzis and El-Zein, 2016;Nigri and Oumeddour, 2016;Mu et al, 2016;Rashvand et al, 2016;Srigley et al, 2016;Farley et al, 2017;Georgouli et al, 2017;Jergović et al, 2017;Liu et al, 2017;Ok, 2017;Philippidis et al, 2017;Santos et al, 2017;Uncu et al, 2017) or the admixture of lower quality or refined olive oils (Nigri and Oumeddour, 2016;Jergović et al, 2017). Although EVOO have a long history of economic adulteration, its detection still is a challenging task due to the diverse composition of cultivars and the limitations of existing detection methods (Ou et al, 2015;Srigley et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, different analytical techniques have been developed to detect olive oil adulterations (e.g., MALDI-TOF/MS technique; mid infrared, Raman, fluorescence or visible spectroscopy; DNA-targeted approaches; ion mobility spectrometry; nuclear magnetic resonance; dielectric technique; ultrasounds technique; gas chromatography; etc. ), namely to identify and/or quantify the addition of other vegetable oils like camellia, canola, corn, grapeseed, hazelnut, peanut, rapeseed, soya, sesame, soybean and sunflower oils (De Melo Milanez and Pontes, 2015;Sun et al, 2015;Alouache et al, 2016;Jabeur et al, 2016;Kalaitzis and El-Zein, 2016;Nigri and Oumeddour, 2016;Mu et al, 2016;Rashvand et al, 2016;Srigley et al, 2016;Farley et al, 2017;Georgouli et al, 2017;Jergović et al, 2017;Liu et al, 2017;Ok, 2017;Philippidis et al, 2017;Santos et al, 2017;Uncu et al, 2017) or the admixture of lower quality or refined olive oils (Nigri and Oumeddour, 2016;Jergović et al, 2017). Although EVOO have a long history of economic adulteration, its detection still is a challenging task due to the diverse composition of cultivars and the limitations of existing detection methods (Ou et al, 2015;Srigley et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Corn oil was used as it closely matches the spectrum and longitudinal relaxation times of subcutaneous abdominal fat [30] and was best described by bimodal T2 distributions and biexponential model for 100% of the voxels [12]. Dairy cream of variable fat content was used as they provide a mixed aqueous and fatty environment with measurable contribution from each component with the short T2 component being indicative of the fat fraction [31].…”
Section: Discussionmentioning
confidence: 99%
“…Free water exhibits pure monoexponential decay with long T2 values while water in tissue bound to lipids and proteins has a different relaxation behaviour with shorter T2 values [9][10][11]. Materials mimicking adipose tissue relaxation such as corn oil present biexponential decay with a shorter and a longer T2 component, indicating the presence of two proton components in the fatty acid chains [12]. Clinical T2 relaxometry sequences measure signal from aqueous or fatty components indiscriminately within a single voxel.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that EVOO significantly differs from polyunsaturated oils extracted from corn, canola, sunflower and soybean. However, this configuration could not distinguish EVOO from HO 24 . Hence, a more effective data mining approach is necessary to exploit the information provided in relaxation curves.…”
Section: Introductionmentioning
confidence: 99%